Inherent Defeatism in Barry Hannah’s “The Agony of T. Bandini” and “Uncle High Lonesome” - Merkel, Julia (Current Objectives of Postgraduate American Studies, 2012)
William Faulkner’s themes and motifs are topical for the (literary) South to the present day, expressed by an inherent defeatism and structural pessimism. This reading of Barry Hannah’s short stories “The Agony of T. Bandini“ and “Uncle High Lonesome“ traces this heritage by identifying Hannah’s settings and psychological environment as ones of anticipated failure and lethargic acceptance of fate.